LA ENSEÑANZA-APRENDIZAJE DE LA HISTORIA COMO RECURSO PARA LA INSERCIÓN SOCIAL DE LOS ADOLESCENTES: THE TEACHING-LEARNING PROCESS OF HISTORY AS A RESOURCE FOR THE SOCIAL INSERTION OF ADOLESCENTS - Guerra Gómez, Sarvelio (Opuntia Brava, 2018)
El artículo referencia los aportes que han realizado autores que en el ámbito de la pedagogía cubana e iberoamericana han incursionado en el tema proponiendo soluciones a uno de los problemas más agudos de la pedagogía mundial: el aporte de la Enseñanza Secundaria Básica. Desde los resultados de un proyecto de investigación sobre la dirección del aprendizaje de los adolescentes, se exponen ideas que se adentran en la experiencia cubana al respecto, tratando de superar el enfoque elitista y tradicional que ha predominado en este nivel durante muchos años. ABSTRACT The article makes reference to the contributions that authors have made in the scope of Cuban and Latin American Pedagogy, where have dealt with the subject having proposed solutions to one of the acute problems of Pedagogy world-wide: the contribution of Basic Secondary Education. From the results of a project of investigation on the direction of the learning of the adolescents, ideas are exposed that are entered on the matter in the Cuban experience, trying to surpass the elitist and traditional approach that has predominated in this level during many years. KEY WORDS: Education of history, adolescents, Didactics of history.